1994
DOI: 10.1159/000276655
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular Involvement in Systemic Sclerosis

Abstract: In order to evaluate the nature and association of audiovestibular disturbances and systemic sclerosis (SSC), 37 unselected SSC patients were studied with a detailed audiological and vestibular examination since November, 1987. Pure-tone audiometry, speech audiometry, impedance audiometry, brainstem response audiometry and vestibular function using electronystagmographic recording were performed. We found a rather frequent audiovestibular involvement (41 %). A hearing loss was found in 14 SSC patients; hearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
43
2
12

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 10 publications
8
43
2
12
Order By: Relevance
“…Of the eight studies that investigated changes, all identified hearing loss in most individuals with SS, and the prevalence in this finding ranged from 20 to 77%. The type of hearing loss was bilateral sensorineural (6,(9)(10)(11)13,16,17) in most cases, corroborating the physiopathology of the systemic disease. However, mixed (11,15,17) and unilateral (13,17) hearing loss were also described in few cases.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Of the eight studies that investigated changes, all identified hearing loss in most individuals with SS, and the prevalence in this finding ranged from 20 to 77%. The type of hearing loss was bilateral sensorineural (6,(9)(10)(11)13,16,17) in most cases, corroborating the physiopathology of the systemic disease. However, mixed (11,15,17) and unilateral (13,17) hearing loss were also described in few cases.…”
Section: Resultssupporting
confidence: 56%
“…The most used study design for describing auditory and vestibular changes in individuals with SS was the crosssectional design, observed in five analyses (10)(11)(12)(13)(14) , followed by four case reports (6,9,15,16) , and one case-control study (17) . Because cross-sectional studies reported findings of a single moment, it was difficult to determine a temporal sequence between exposure to a specific factor and the subsequent development of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations